Factor Stability of the Adam's Perceived Wellness Survey: Adam’s 個人康盛評價量表的因子穩定性 - FUNG, Lena; PANG, Jofy (Asian Journal of Physical Education & Recreation, 2010)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. Composites of wellness have been conceptualized as having six, seven, eight, or more dimensions depending on the theoretical bias of individual scholar. This paper aims to introduce an instrument that can be used to evaluate the six dimensions commonly accepted as the basic essential elements of wellness and to report on the factor stability of the instrument with data collected from a sample of university students studying in Hong Kong. This instrument is the Perceived Wellness Survey developed by Adams and his associates. 現今用以測量個人康盛概況的自評量表頗多，本文旨在介紹一個精簡而能完整地測量個人康盛概況的量表及其因子的穩定性。